Yin Yang 1 (YY1)-induced long intergenic non-protein coding RNA 472 (LINC00472) aggravates sepsis-associated cardiac dysfunction via the micro-RNA-335-3p (miR-335-3p)/Monoamine oxidase A (MAOA) cascade. Issue 1 (1st January 2022) - Mo, Guixi; Mo, Jian; Tan, Xiujuan; Wang, Jingjing; Yan, Zhenyi; Liu, Yijun
ABSTRACT: As a leading complication of sepsis, sepsis-induced cardiac dysfunction (SICD) contributed to the high mortality of patients with sepsis. Long non-coding RNA (LncRNA) LINC00472 has been reported to be in sepsis-induced disease. Nonetheless, its biological function and underlying molecular in SICD remain largely unknown. In this study, in vivo and in vitro SICD models were established via LPS treatment. H&E staining was employed for the evaluation of myocardial injury. ELISA assay was performed to detect cardiac Troponin I (cTnI), creatine kinase-MB (CK-MB), interleukin (IL)-1β, and tumor necrosis factor-α (TNF-α) levels. Cardiomyocyte viability and apoptosis were assessed via CCK-8 and flow cytometry assays. The transcriptional regulation of YY1 on LINC00472 was demonstrated via ChIP assay. Besides, the interaction between YY1 and LINC00472, as well as the association between miR-335-3p and LINC00472 or MAOA were verified via luciferase reporter assay and RNA immunoprecipitation (RIP) assay. Herein, highly expressed LINC00472 was observed in both in vivo and in vitro SICD models. LINC00472 knockdown substantially attenuated LPS-induced inhibition on cardiomyocyte viability and reversed cardiomyocyte apoptosis and inflammatory response mediated by LPS treatment. YY1 induced LINC00472 upregulation, thereby promoting cardiomyocyte dysfunction induced by LPS. In addition, MAOA upregulation or miR-335-3p inhibition could partly reverse the suppressive effect on LPS-induced cardiomyocyte dysfunction mediated by LINC00472 knockdown. Based on our results, it seemed that YY1-activated LINC00472 might contribute to SICD progression via the miR-335-3p/MAOA pathway.